Skill versus reliability in venture capital - Khanna, Naveen; Mathews, Richmond D. (Journal of Financial Economics, 2022)
We study competition for startups among VCs with heterogeneous skill. VCs with established skill face two impediments. First, less established VCs compete aggressively for new startups in order to establish a reputation. Second, startups also value reliability in their VCs, which imposes a higher cost on established VCs because they have better outside options. As a result, startups “over-experiment” by excessively partnering with less established VCs, which crowds out established skill and reduces social welfare. Established VCs are hurt because they need to pay more to attract startups, lose profitable opportunities, and face increased competition from newly established VCs.